Sex differences in the association between symptoms and superoxide dismutase in patients with never-treated first-episode schizophrenia. (28th May 2021) - Wang, Dong Mei; Chen, Da Chun; Wang, Li; Zhang, Xiang Yang
Abstract: Objectives: Considering the sex differences and oxidative stress in the pathophysiological mechanism of schizophrenia (SCZ), we explored the sex differences in clinical characteristics and superoxide dismutase (SOD) activity as well as their relationship in never-treated first-episode (NTFE) patients with SCZ in the Han Chinese population, which has not been reported yet. Methods: Total SOD and manganese SOD (MnSOD) activities were examined in 165 NTFE patients with SCZ (male/female = 98/67) and 133 healthy controls (male/female =70/63). Psychopathological symptoms were evaluated by a five-factor model of the Positive and Negative Syndrome Scale (PANSS). Results: SCZ patients had higher plasma total SOD activity than healthy controls ( p < .01). In healthy controls, the total SOD activity was significantly higher in males than that in females ( p < .001), but not in patients group ( p > .05). Further, Multiple regression analysis revealed that in male patients, the PANSS depressive factor was independently positively correlated with MnSOD or total SOD activity (both p < .01), while in female patients, the MnSOD activity was positively related to the PANSS positive symptom score ( p < .05). Conclusions: Our findings indicate sex differences in the relationship between SOD activities and psychopathological symptoms in the early stage of SCZ.